Penerapan Reward and Punishment dalam Meningkatkan Kedisiplinan pada Kegiatan Pembelajaran Tematik Siswa Kelas II MI Al-Maghfiroh - Zuliani, Rizki; Nirmalasari, Endah; Ramadhinia, Nadya (TSAQOFAH, 2023)
Students like to be given rewards because they can motivate them to do something. In addition, there is a sense of satisfaction in itself after doing something that is then given a reward. In contrast to rewards, giving punishment actually gets a lot of rejection from students such as Presentation Punishment, Deletion Punishment and Time out, these punishments make students feel ashamed and deterrent so students correct their mistakes. Based on observations made at MI Al-Maghfiroh it can be seen that, when researchers made observations in class II in thematic learning there were still students who lacked discipline, such as arriving late, chatting while the teacher was explaining thematic learning, making noise when thematic learning, not doing assignments or homework given by thematic teachers, dressing untidy according to the standards that apply during thematic learning. This type of research is Classroom Action Research (PTK) or Classroom Action Research. The method or method of approach used in this research is class-based research and is carried out in class. This type of research is also accompanied by a questionnaire specifically for students in order to find out how students respond to disciplinary attitudes at school. Through this CAR, researchers have tried to apply rewards and punishments in increasing discipline in thematic learning activities for Class II MI Al-Maghfiroh students. The research was carried out in four steps, namely: (1) Planning, (2) Implementation and Observation 3) Observation 4) Reflection